Allopregnanolone Decreases Evoked Dopamine Release Differently in Rats by Sex and Estrous Stage - Dornellas, Ana Paula S.; Macedo, Giovana C.; McFarland, Minna H.; Gómez-A, Alexander; O’Buckley, Todd K.; Da Cunha, Claudio; Morrow, A. Leslie; Robinson, Donita L. (Frontiers in Pharmacology, 2021)
Mesolimbic dopamine transmission is dysregulated in multiple psychiatric disorders, including addiction. Previous studies found that the endogenous GABAergic steroid (3,5)-3-hydroxy-5-pregnan-20-one (allopregnanolone) modulates dopamine levels in the nucleus accumbens and prefrontal cortex. As allopregnanolone is a potent positive allosteric modulator of GABAA receptors, and GABAA receptors can regulate dopamine release, we hypothesized that allopregnanolone would reduce phasic fluctuations in mesolimbic dopamine release that are important in learning and reward processing. We used fast-scan cyclic voltammetry in anesthetized female and male rats to measure dopamine release in the nucleus accumbens evoked by electrical stimulation of the ventral tegmental area, before and after administration of allopregnanolone. Allopregnanolone (7.5–25mg/kg, IP) reduced evoked dopamine release in both male and female rats, compared to β-cyclodextrin vehicle. In males, all doses of allopregnanolone decreased dopamine transmission, with stronger effects at 15 and 25mg/kg allopregnanolone. In females, 15 and 25mg/kg allopregnanolone reduced dopamine release, while 7.5mg/kg allopregnanolone was no different from vehicle. Since allopregnanolone is derived from progesterone, we hypothesized that high endogenous progesterone levels would result in lower sensitivity to allopregnanolone. Consistent with this, females in proestrus (high progesterone levels) were less responsive to allopregnanolone than females in other estrous cycle stages. Furthermore, 30mg/kg progesterone reduced evoked dopamine release in males, similar to allopregnanolone. Our findings confirm that allopregnanolone reduces evoked dopamine release in both male and female rats. Moreover, sex and the estrous cycle modulated this effect of allopregnanolone. These results extend our knowledge about the pharmacological effects of neurosteroids on dopamine transmission, which may contribute to their therapeutic effects.